Role of the transtheoretical model of behavior change in quitting smoking and gambling disorder together - Fidancı, İzzet; Öncü, Muhammet Zahid; Öztürk, Onur (Journal of Dependence, 2020)
The reason why gambling increased and diversified for 3500 years is its characteristics of developing an addiction. Smoking, which is usually associated with gambling addiction, can be caused by the fact that smoking is used to give pleasure or keep away from stress. Transtheoretical model, which can be used in addiction treatments, can be effective in recovering from both gambling and cigarette addictions when used together to treat both addictions. The aim of this article was to emphasize that there may be the same coexistence in treatment approaches due to the relationship of addictions with each other.
Keywords: Gambling; smoking; addiction; transtheoretical model of behavior change